Bibliometric analysis and text mining to reveal research trends on fruit by-products under circular economy strategies - Camacho Orbegoso, Ever William (2023)
Fruit processing generates large amounts of by-products (BPs) that play a key role in the economic, social and environmental crisis. Although these residues are not usually used, they have better nutritional and bioactive value than the edible part. Considering that the circular economy is a sustainable approach to promote a zero waste processing system, the objective of this study was to use bibliometric analysis and data mining to provide a body of knowledge on trends in the field of research on fruit BPs under circular economy strategies. The publication of the SDGs has stimulated the adoption of circular economy strategies to use fruit BPs, which was reflected in the growth of scientific production since 2015. Although it is suggested that the field of study is at an exponential stage, development is limited by the lack of regulatory instruments to regulate the use of fruit BPs. The authorship analysis showed that over time a large number of authors have participated in scientific production and several research groups were formed, but temporarily. However, it is expected that the rise of this field will attract the attention and permanence of the authors. At the country level, the European Union leads in scientific production with outstanding socioeconomic and cultural benefits, which is slowly being replicated in developing countries. Keyword analysis showed that the main trend is the green recovery of high-value compounds. To meet other needs, other trends include the use of fruit BPs to develop functional ingredients, compost, biofuel, packaging materials and for water treatment. Information on the challenges of using these residues was also included. The results will serve as a basis for researchers, entrepreneurs and policy makers in the transition to the circular economy to contribute to sustainability.